2018
DOI: 10.1002/jper.18-0450
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional analysis of risk factors for subclinical periodontitis; active matrix metalloproteinase‐8 as a potential indicator in initial periodontitis in adolescents

Abstract: Background The aim of this study was to investigate how different patient‐related risk indicators might be associated with the odds of developing subclinical periodontitis in adolescents. Methods This cross‐sectional study included 252 Finnish individuals aged 15 to 16 years, of whom 141 were boys and 111 girls. A specially trained dentist performed clinical examinations: measurements included periodontal indexes (bleeding on probing, visible plaque index, root calculus, and probing depth, smoking by pack‐year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
2
19
1
Order By: Relevance
“…Recent investigations showed MMP-8 to be an indicator especially for early periodontitis [20,21]. In the current study, MMP-8 in the gingivitis and periodontitis groups showed signi cant higher compared to the healthy group, but there was no signi cant difference between periodontitis and gingivitis group.…”
Section: Discussioncontrasting
confidence: 40%
“…Recent investigations showed MMP-8 to be an indicator especially for early periodontitis [20,21]. In the current study, MMP-8 in the gingivitis and periodontitis groups showed signi cant higher compared to the healthy group, but there was no signi cant difference between periodontitis and gingivitis group.…”
Section: Discussioncontrasting
confidence: 40%
“…The aMMP-8 PoC test also has the potential to enhance the periodontal risk assessment of patients. As has been suggested by Heikkinen et al [2], the aMMP-8 PoC test result could be used together with other patient-related risk factor information, e.g., gender, use of tobacco products, as well as oral health habits, such as toothbrushing, to create an even more accurate periodontal disease risk profile for patients. Moreover, Räisänen et al [22] recently reported a strong association between patient’s aMMP-8 PoC test results and his/her periodontal treatment needs (CPITN) among adolescents and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Activated matrix metalloproteinase-8 (MMP-8) is a major destructive collagenase in periodontitis [1] but, also, a potential biomarker for initial periodontitis/subclinical periodontitis/pre-periodontitis as well as periodontitis [1,2,3,4,5]. According to several studies [1,2,6,7,8,9,10,11], the progression of periodontitis is reflected as an excessive elevation and activation of MMP-8 in oral fluids. This stage can be measured using a point-of-care lateral flow collagenase-2 immunotest [1,12,13,14,15,16,17,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria were adolescents aged 15 to 16 y living in Kotka and without any orthodontic treatment history and mixed dentition. All participants were examined clinically and, based on a questionnaire, details about general health and health habits (e.g., smoking) registered (Heikkinen et al 2008, 2010, 2016, 2018). Those who were smoking daily or weekly were considered current smokers.…”
Section: Methodsmentioning
confidence: 99%
“…The groups were formed in the following way: healthy group if full-mouth BOP <20 without deep periodontal pockets, gingivitis group if BOP ≥20 without deep periodontal pockets, and subclinical periodontitis group if they had deep periodontal pockets. In the subclinical periodontitis, not all of the clinical or x-ray manifestation symptoms required to diagnose periodontitis are present; mainly gingival bleeding and shallow periodontal pockets exist (Heikkinen, Pakbaznejad, et al 2017; Heikkinen, Raivisto, et al 2017; Heikkinen et al 2018; Räisänen et al 2019). Subclinical periodontitis corresponds to stage I periodontitis, according to the new classification of periodontal diseases (Caton et al 2018).…”
Section: Methodsmentioning
confidence: 99%